Kokonaistaloudellisia ongelmia. 2 - (:unkn) unknown (Tilastokeskus, 1975)
Sisältää artikkeleita useilta kirjoittajilta.
Keywords: tilastot; kansantalouden tilinpito; panos-tuotosanalyysi; rahoitustilinpito; Tutkimuksia, Working Papers